Characteristics of cryptogenic stroke in cancer patients. Issue 4 (11th February 2016) - Gon, Yasufumi; Okazaki, Shuhei; Terasaki, Yasukazu; Sasaki, Tsutomu; Yoshimine, Toshiki; Sakaguchi, Manabu; Mochizuki, Hideki
Abstract: Objective: To clarify the characteristics of cryptogenic stroke in patients with active cancer. Methods: Patients with or without cancer diagnosed with acute ischemic stroke between January 2006 and February 2015 were extracted from a prospectively collected stroke database of Osaka University Hospital. Patients were categorized according to the presence of active cancer and known stroke mechanisms. Results: Among 1191 patients with acute ischemic stroke, 145 (12%) had active cancer. Patients with active cancer were diagnosed more often with cryptogenic stroke than were patients without cancer (47% vs. 12%, P < 0.001). Compared with cryptogenic stroke patients without cancer, cryptogenic stroke patients with active cancer had fewer atherosclerotic risk factors, lower nutrition status, higher plasma D‐dimer levels, and multiple vascular lesions. In a multivariate logistic analysis, plasma D‐dimer level (odds ratio [OR] per 1 standard deviation increase: 6.30; 95% confidence interval [CI]: 2.94–15.69; P < 0.001), and the presence of multiple vascular lesions (OR: 6.40; 95% CI: 2.35–18.35; P < 0.001) were independent predictors of active cancer. When comparing active cancer patients who had known stroke mechanisms with those who had cryptogenic stroke, high plasma D‐dimer levels, multiple vascular lesions, and receiving chemotherapy and/or radiation therapy were associated with cryptogenic stroke etiology. Interpretation: In cryptogenic stroke, patients with active cancer has a unique pathology characterized by high plasma D‐dimer levels and multiple vascular lesions. The hypercoagulable state and malnutrition due to cancer and its treatments potentially influence the development of cryptogenic stroke in cancer patients.